Hydrodynamic response and produced power of a combined structure consisting of a spar and heaving typewave energy converters - Michailides, Constantine (My University, 2021)
During the past years, researchers have studied both numerically and experimentally multibody wave-wind combined energy structures supporting wind turbines and different types of Wave Energy Converters (WECs); rigid body hydrodynamic assumptions have been adopted so far for the development of their numerical models and the assessment of their produced power. In the present paper a numerical model that is based on the use of generalized modes addressing wave-structure interaction effects for the case of a multibody wave-wind combined structure is developed and presented. Afterwards, the developed numerical model is used for the assessment of the hydrodynamic response and the prediction of the produced power of different possible configurations of the updated WindWEC concept which consists of a spar supporting a wind turbine and one, two, three or four heaving type WEC buoys. The combined effects of the center-to-center distance of the WEC and spar platform, the number of the WECs and the grid configuration of spar and WECs on the hydrodynamic interaction between the different floating bodies, spar and WEC buoys, and consequently on their response and wave power production are examined for regular and irregular waves. Strong hydrodynamic interaction effects exist for small distance between spar and WECs that result to the decrease of the produced power. Power matrices of the updated WindWEC concept are presented for all examined configurations with different number of WECs. Moreover, the annual produced power of the updatedWindWEC in two sites is estimated and presented. The generalized modes analysis presented in this paper is generic and can be used for the early stage assessment of wave-wind combined energy structures with low computational cost. The updated WindWEC can be used in sea sites with different environmental characteristics while extracting valuable amount of wave power.
Keywords: Generalized modes; Hydrodynamic analysis; Combined energy structures; Offshore wind turbines; Wave energy converters; WindWEC